Analysis of Optimal Stock Performance Using the Discounted Cash Flow Method and Stock Price Forecasting Using the Holt-Winters Method: (Case Study: Shares of PT Perusahaan Gas Negara Tbk) - Miasih, Sekar; Rohaeti, Embay; Wijayanti, Hagni (CV. Publikasi Indonesia, 2024)
The high liquidity of PT Perusahaan Gas Negara Tbk shares and significant fluctuations in share prices create uncertainty that requires in-depth analysis. Stock performance analysis is carried out with 2 stages in outline, namely the stages of fundamental analysis and technical analysis. Fundamental analysis is carried out to analyze optimal stock performance, one of which is by using the discounted cash flow (DCF) method. Technical analysis is used to determine the condition of stock performance in the future by forecasting stock prices using the Holt-Winters forecasting method. The objectives of this study are to analyze optimal stock performance, forecast stock prices, and evaluate forecasting results. The data used is PGN's 2023 annual report and daily data on PGN's stock price for the period January 1, 2019, to December 31, 2023, totalling 1,231 data. The results of the optimal stock performance analysis show that PGN's stock performance is declared optimal with an intrinsic value of 3,149.18, which is greater than the current stock price (undervalued). The results of stock price forecasting show that the forecasting results follow the actual data pattern, with an accuracy value using MAPE (mean absolute percentage error ) of 10.9%, it is stated that the forecasting performance has performed well.